Interaksi Sosial antar Umat Beragama di Kecamatan Lut Tawar Aceh Tengah - Indah Permata Sari (Jurnal Sosiologi Agama Indonesia (JSAI), 2020)
This article aims to discuss the views of in Lut Tawar Subdistrict regarding religious life that occurs within society, especially the relationship between religious people. Also the supporting factors, barriers, social interactions between religious people. The authors use a qualitative approach with data collection techniques is observation, interview, and literature studies. This research concluded that the relationship between religious people in Lut Tawar Sub-district is well and that based on the absence of conflict that occurs among religious people. It is also supported by a tolerance perspective on other religions. The social conduciveness of the society base on the strong historical foundation behind the process of social interaction among religious people. Then, society also instilled the principle of respect and appreciated each individual who ultimately created social harmony. Besides, there is a role of religious figures that always keep the tolerance perspective between religious people intertwined.